(3PNQ GdeJCgdjf hGdfSG aj eYQaI GdCWgGQ hGdOeGs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj LYd GdQLGd Ydi GdfSGA bhGejf hCeQge HhYXgf hGdJCOjH hJYdje GdOjf hHYO abO GJab GdabgGA Ydi aQVjI Yde GdMGd aeYQaI GdOeGA GdeNJUI HGdfSGA hGLHI Ydjgf hdG jejRhf Hjf GdUMjMI ef GdOeGA hGdCWgGQ GdaGSOI aCQOJ Cf CUfa QSGdI MGhjI deSGFd MGhjI Yf PcQ NdGa heHGMK ZjQ egeI (B--s
(3BNQgG (B:s
(3heG CUGH KhH GdeYPhQ CcKQ ef bOQ GdOQge aYdjg ZSdg Ef cGf eajOG (B( (3cPG (B) (3hEf cGf HMGd dh ZSdg KGfjG bHd GdaQGZ ef GdUdGI LGR Cf dG jaSOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 61s
(3eYLe GdeDdajf (B3 / 176s
(3cTa GdXfhf (B1 / 822s
(3gOjI GdYGQajf (B2 / 252s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs